Error performance analysis of forward error correction using convolutional encoding in the presence of (1/f) noise - Yasin Yousif Al-Aboosi; Ammar Ali Sahrab; Amal Ibrahim Nasser; Hussein A. Abdulnabi (Institute of Advanced Engineering and Science, 2023)
Any communication scheme's principal goal is providing error-free data transmission. By increasing the rate at which data could be transmitted through a channel and maintaining a given error rate, this coding is advantageous. The message bits to be transmitted will gradually receive more bits thanks to the convolution (channel) encoder. At the receiver end of the channel, a Viterbi decoder is utilized in order to extract original message sequence from the received data. Widely utilized error correction approaches in communication systems for the enhancement of bit error rate (BER) performance are Viterbi decoding and convolutional encoding. The Viterbi decoder and convolution encoder rate for constraints with lengths of 2 and 6 and bit rates of 1⁄2 and 1⁄3 are shown in this study in the presence of (1/f) noise. The performance regarding the convolutional encoding/hard decision Viterbi decoding forward error correction (FEC) method affects the simulation outcomes. The findings demonstrate that the BER as function of signal to noise ratio (SNR) acquired for uncoded binary phase shift keying (BPSK) with the existence of additive white Gaussian noise (AWGN) is inferior to that acquired with the use of a hard decision Viterbi decoder.